Demografien, den økonomiske krise og sundhedsvæsenet - Pedersen, Kjeld Møller (Politik, 2012)
Danish forecasts for 2040 of the economic consequences of population ageing and longer life expectancy are critically reviewed. Alone for 2010-2020 an annual increase in spending of 4-5 billion Dkr is needed accord- ing to the best estimates. To this is added the consequences of the economic crisis. e annual growth rate has come down from 3,3% p.a. to close to 1%. is situation is put into perspective by looking at the scal sustainability of the whole public sector and how much health care adds to the challenge of staying scal sustainable: At least 0,7% of BNP out of a sustainability index of 1,1% is due to health care. No coherent strategy for coping with demographics and the economic crisis has been developed. A number of initiatives are discussed and evaluated: Increased productivity, elimination of the costs of bad quality in health care, tougher prioritization by changing indication levels for treatment, and increased preventive activities, e.g. readmission to hospital. At present no radical reform proposal for the health care sector are discussed.